2015
DOI: 10.1111/ijlh.12380
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 46/1 haplotype is associated with JAK2 V617F – positive myeloproliferative neoplasms in Brazilian patients

Abstract: In agreement with previous reports, JAK2 46/1 haplotype for JAK2 V617F was associated with cMPN positive in Brazilian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…The significant associations between SNPs closest to these two lncRNAs and partial HP indicated that SNPs nearby PRANCR and TNK2–AS1 could be regarded as potential molecular markers affecting the immunity of dairy cows. In other studies, the association between SNPs and HP is also widely investigated [ 57 , 58 ], but the causal mutation within these two lncRNAs should be further explored for future animal breeding.…”
Section: Discussionmentioning
confidence: 99%
“…The significant associations between SNPs closest to these two lncRNAs and partial HP indicated that SNPs nearby PRANCR and TNK2–AS1 could be regarded as potential molecular markers affecting the immunity of dairy cows. In other studies, the association between SNPs and HP is also widely investigated [ 57 , 58 ], but the causal mutation within these two lncRNAs should be further explored for future animal breeding.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are contained in sites of single-base genetic alterations called single nucleotide variants (SNVs), which contribute to interindividual and inheritable differences in complex phenotypes [ 74 , 75 ]. A group of genetic variations present on the same chromosome, which are not easily separable by recombination and therefore tend to be inherited together, is called a haplotype [ 76 ].…”
Section: 46/1 Haplotypementioning
confidence: 99%
“…rs10974944 was the first to be associated with the emergence of MPNs [ 98 ]. Studies carried out in Europe, Japan, China, North America, and Brazil have shown that the variant allele of rs10974944 (G) is more frequent in all MPN patients (especially those positive for JAK2V617F) than in the control population [ 68 , 76 , 89 , 98 , 99 , 100 ].…”
Section: 46/1 Haplotypementioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies found that rs10974944 was associated with the development of V617F‐positive MPNs (Jones et al, 2009; Kilpivaara et al, 2009; Tanaka et al, 2013). This observation might be due to the linkage between the JAK2 46/1 and V617F as many studies had demonstrated that this haplotype was associated with V617F‐positive myeloproliferative neoplasms in Brazilian (Macedo et al, 2015), Romanian (Trifa et al, 2010), Japanese (Tanaka et al, 2013) and other populations (Anelli et al, 2018; Stolyar et al, 2018). However, the results of our study indicated that in the Vietnamese population, the linkage disequilibrium between rs10974944 and rs77375493 (V617F) was not tight, yet rs10974944 still had a strong association with MPNs, suggested that the effect of rs10974944 on MPNs phenotype was independent of V617F profile.…”
Section: Discussionmentioning
confidence: 99%